Innovation of Money Offering in Digital Landscape of Sharia Perspective: Challenges and Prospects - Anisa Lestari; Umi Khozinatul Khoiriyah (Penerbit Hellow Pustaka, 2025)
The presence of digital money does offer various benefits, such as ease of transactions, cost efficiency, and financial inclusion. However, the development of digital money also poses various challenges, especially in the context of sharia. Therefore, research is needed to understand the challenges and prospects of innovation in digital money offerings from a sharia perspective. The method used in this study is a descriptive method, namely the procedure for collecting data through literature searches and reference analysis. The literature study approach involves a number of tasks including compiling research sources, reading and taking notes, and using library data collection techniques. This study explores various aspects related to innovation in money offerings in the digital landscape, identifying the challenges faced, and evaluating its future prospects. Through a sharia approach, we hope to provide valuable insights for readers on how the digital revolution has influenced and will continue to shape the global sharia financial system.